2017
DOI: 10.1186/s12985-017-0701-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and complete genome of the virulent Myoviridae phage JD007 active against a variety of Staphylococcus aureus isolates from different hospitals in Shanghai, China

Abstract: BackgroundThe implementation of phage therapy is re-emerging with the increase in widespread antibiotic-resistant bacteria.Methods Staphylococcus phage JD007 was characterized and its complete genome sequence analysed.Results Staphylococcus phage JD007 was classified as belonging to the Myoviridae family based on its morphology, as observed by transmission electron microscopy. Its lytic activity was stable between pH 5–11 and below 42 °C; moreover, an absorbance curve showed that nearly 90% of the viral partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…Characterization of staphylococcal lysin derived from phage JD007. A previous study demonstrated that phage JD007 exhibits strong antibacterial activity against various types of S. aureus strains (25). In this study, a lysin was identified from the whole-genome sequence of phage JD007 (JDlys).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Characterization of staphylococcal lysin derived from phage JD007. A previous study demonstrated that phage JD007 exhibits strong antibacterial activity against various types of S. aureus strains (25). In this study, a lysin was identified from the whole-genome sequence of phage JD007 (JDlys).…”
Section: Resultsmentioning
confidence: 95%
“…Escherichia coli strains, used for gene cloning and producing recombinant proteins, were cultured aerobically in Luria-Bertani (LB) broth with shaking (180 rpm) at 37°C. The JD007 phage was kindly provided by ZeLin Cui (Shanghai General Hospital, Shanghai, China) (25). Purification and genomic DNA extraction were performed as described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…These variant Kayviruses represent thus interesting starting material to address different molecular steps of the phage-host interaction process. The maintenance of a Kayvirus in all commercial products from commercial Eastern phage cocktails is also explained by the exceptionally broad host range of this phage, which achieves, 60% to >95% coverage when tested against different collections of S. aureus clinical isolates (Hsieh et al, 2011;Alves et al, 2014;Cui et al, 2017). Phage K, the prototype of Kayviruses, binds to the highly-conserved wall-teichoic acids (WTA) on the surface of the S. aureus cell wall, which explains its broad host range (O'Flaherty et al, 2005;Xia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate thermal stability, 100 μl of the bacteriophage suspension (10 8 PFU/ml) was added to 900 μl of elution buffer and incubated at different temperatures (37, 42, 50, 60, 70, and 80°C) for 2 h (20). After the incubation period, the phage titer was determined through the double-layer agar method ( Cui et al, 2017 ). The assays were carried out at three independent times in triplicate.…”
Section: Methodsmentioning
confidence: 99%